Neurological Deficits After Long-term Pyrethroid Exposure. (22nd March 2017) - Hansen, Martin Rune Hassan; Jørs, Erik; Lander, Flemming; Condarco, Guido; Debes, Fróði; Tirado Bustillos, Noemi; Schlünssen, Vivi
Pyrethroid pesticides have been suggested to be a cause of Parkinson disease and other neurodegenerative diseases. To investigate this, a cross-sectional study was conducted among 120 Bolivian public health vector program spray men, primarily exposed to pyrethroids. Pesticide exposure and central nervous system (CNS) symptoms were determined by a structured interview, whereas neuromotor and neurocognitive performance was assessed using the computerized Behavioral Assessment and Research System and CATSYS system. Individuals exposed to higher levels reported significantly more CNS symptoms (adjusted odds ratio per quintile of cumulative exposure = 2.01 [1.22-3.31]). There was no association seen between pyrethroid exposure and neuromotor performance. Higher spraying intensity was associated with significantly worse neurocognitive performance in structural equation models (adjusted β per quintile = −0.405 [−0.660 to −0.150]), and workers only exposed to pyrethroids performed worse than workers also exposed to other pesticides (adjusted β = −1.344 [−2.224 to −0.464]). Chronic pyrethroid exposure may cause deterioration in neurocognitive performance, and exposure control is recommended.